On the type species of the South American dung beetle genus Chalcocopris Burmeister, 1846 (Coleoptera: Scarabaeidae: Scarabaeinae), with some comments on the type locality of C. hesperus (Olivier, 1789) - Cupello, Mario; Rossini, Michele; Vaz-De-Mello, Fernando Z. (Zootaxa, 2016)
Recently, a new paper authored by two of us (Rossini & Vaz-de-Mello, 2015) addressed a taxonomic revision of Chalcocopris Burmeister, 1846, describing a second species for the genus and expanding our knowledge of its distribution and morphological diversity. In the present work, we address additional nomenclatural and historical issues not covered in that paper.